Nuevos hallazgos en la polinización de orquídeas brasileñas - Singer, Rodrigo B. (Universidad de Costa Rica, 2016)
Because of their remarkable flower morphology, orchids are particularly interesting objects of study. Most orchid species hold their pollen in discrete packs, so-called pollinia (singular; pollinium). These pollinia, together with other pollinium stalks, form more or less complex translatory units, so-called pol- linaria (singular: pollinarium).